Relationship between cooling rate and crystallization behavior of hydrogenated sunflowerseed oil - Herrera, María Lidia (1992)
The relationship between cooling rate and crystallization behavior of hydrogenated sunflowerseed oil and its thermal properties during melting were investigated by differential scanning calorimetry and x-ray diffraction. At crystallization, temperature peaks and area percents of components with higher melting points were found to be greater when cooling rate was slower. When samples were melted, total enthalpies were similar at all rates. According to the chemical composition of the analyzed samples, the components with higher melting points were found in samples with a higher saturated fatty acid content. Changes in the profile of melting curves might be due to differences in triglyceride intersolubility.